Enhancing Cultural Wealth: Positioning as a Language Broker across School and Home. Issue 3 (3rd July 2019) - Yoo, Monica S.
Abstract : This article examines how students from immigrant families position themselves during language brokering acts that blur the boundaries between home and school. It draws upon a community cultural wealth framework (Yosso, 2005), which attends to the cultivation and uptake of rich forms of capital from culturally and linguistically diverse communities, to explain how and why student language brokers might take up particular literacy practices infused with both authoritative and internally persuasive discourses (Bakhtin, 1981). As these two kinds of discourse relate to how students may (re)position themselves during the brokering process, the author explores the ways in which authoritative and internally persuasive discourses and particular forms of capital intersect as students engage in brokering that is intended to increase their family's overall cultural wealth and future success.